A Review of Proliferative Vascular Disorders of the Central Nervous System of Animals. Issue 5 (September 2021) - Marr, Jacqueline; Miranda, Ileana C.; Miller, Andrew D.; Summers, Brian A.
In disease, blood vessel proliferation has many salient roles including in inflammation, when granulation tissue fills superficial defects, or in the recanalization of an occluded blood vessel. Sometimes angiogenesis goes awry—granulation can be exuberant, and plexiform proliferation of vascular components can contribute to pulmonary hypertension. This review focuses on the diverse manifestations of pathologic vascular overgrowth that occur in the brain, spinal cord, and meninges of animals from birth until old age. Entities discussed include systemic reactive angioendotheliomatosis in which glomeruloid vascular proliferations are encountered in various organs including the central nervous system (CNS). The triad of CNS vascular malformations, hamartomas, and benign vascular proliferations are an especially fraught category in which terminology overlap and the microscopic similarity of various disorders makes diagnostic classification incredibly challenging. Pathologists commonly take refuge in "CNS vascular hamartoma" despite the lack of any unique histopathologic features and we recommend that this diagnostic category be abandoned. Malformative lesions that are often confusing and have similar features; the conditions include arteriovenous malformation, cavernous angioma, venous angioma, and capillary telangiectases. Meningioangiomatosis, a benign meningovascular proliferation with dual components, is a unique entity seen most commonly in young dogs. Last, accepted neoplastic conditions range from lower-grade locally acquired growths like hemangioblastoma (a tumor of mysterious interstitial stromal cells encountered in the setting of abundant capillary vasculature proliferation), the rare hemangioendothelioma, and the highly malignant and invariably multifocal metastatic hemangiosarcoma. Additionally, this review draws on the comparative medical literature for further insights into this problematic topic in pathology.